Efektivitas Storytelling dan Role-Play dalam Pembelajaran Bahasa Arab di MI/SD Indonesia - Muhammad Fariq Heemal Attruk; Budi Satriadi (Al-Qalam: Jurnal Pendidikan Bahasa Arab, 2026)
Learning Arabic in Indonesian Islamic elementary schools is often teacher‑centred, with low student motivation and little active language use. Storytelling and role‑play are seen as promising, but solid evidence is still scattered. This article reviews and critically evaluates existing studies on both methods. A narrative literature review was done by searching Scopus and Google Scholar for 2016-2026. After applying clear inclusion criteria, seven empirical studies on MI/SD students in Indonesia were selected and analysed thematically. The results show storytelling helps vocabulary, listening, and speaking confidence. Role‑play boosts active participation, social interaction, and speaking skills. One study combined both with good results. However, most studies used classroom action research without control groups, small samples, unvalidated tools, short periods, and focused only on Islamic schools in Java. No longitudinal or direct comparison studies exist. Overall, storytelling and role‑play show clear promise, but current evidence remains preliminary. Stronger research designs are needed. Practical tips for teachers are also provided.